2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793648
|View full text |Cite
|
Sign up to set email alerts
|

Attention-based Lane Change Prediction

Abstract: Lane change prediction of surrounding vehicles is a key building block of path planning. The focus has been on increasing the accuracy of prediction by posing it purely as a function estimation problem at the cost of model understandability. However, the efficacy of any lane change prediction model can be improved when both corner and failure cases are humanly understandable. We propose an attentionbased recurrent model to tackle both understandability and prediction quality. We also propose metrics which refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
(29 reference statements)
0
30
0
Order By: Relevance
“…Notably, for cut-in and cut-out, two behavior that have a significant impact on the driving status of ego-vehicle, our model achieves the best performance compared to Social-LSTM and has increased by 6.2% and 6.9% respectively, and the overall prediction accuracy has improved significantly. In the multi-parameter evaluation system, it is compared with dynamic Bayesian networks [35], HSS based LSTM [36], attention-based LSTM [37], and Bayesian networks [38], as shown in Table 3. As shown in Table 3, compared with the dynamic Bayesian network, the F1 score, precision, and accuracy are increased by 16.2%, 31.2%, and 36.9%, respectively, and the recall is slightly reduced by 8.8%.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, for cut-in and cut-out, two behavior that have a significant impact on the driving status of ego-vehicle, our model achieves the best performance compared to Social-LSTM and has increased by 6.2% and 6.9% respectively, and the overall prediction accuracy has improved significantly. In the multi-parameter evaluation system, it is compared with dynamic Bayesian networks [35], HSS based LSTM [36], attention-based LSTM [37], and Bayesian networks [38], as shown in Table 3. As shown in Table 3, compared with the dynamic Bayesian network, the F1 score, precision, and accuracy are increased by 16.2%, 31.2%, and 36.9%, respectively, and the recall is slightly reduced by 8.8%.…”
Section: Results Analysismentioning
confidence: 99%
“…This paper proposes a target vehicle road-right change intention prediction method based on the interactive information of a five-vehicle In the interweaving area, which is not considered in SA-LATM [33] and SVM + ANN [34], this paper realizes that it does not depend on the external environment information to effectively predict the interaction intentions of the surrounding vehicles to the ego-vehicle. The A-LSTM [37] uses the distance of the on-/off-ramp to solve the prediction in the interweaving area. However, there are various forms of access ramps in the expressway scene.…”
Section: Discussionmentioning
confidence: 99%
“…In [27], a new spatial–temporal attention model validated on NGSIM data sets [28] was proposed to alleviate the problem that past attention mechanisms in the trajectory task lacked explainability. The authors in [29, 30] are also excellent works that used attention‐based RNN models to do the trajectory prediction task.…”
Section: Related Workmentioning
confidence: 99%
“…It mainly consists of mandatory lane change (to make drivers keep following their route) and discretionary lane change (to pursue a better driving condition) [13]. Some studies indicated that a lane change is one of the major sources of traffic oscillations and collision risks [14]. In previous studies, traditional lane change models only consider unidirectional effects of surrounding vehicles on the subject vehicle, such as Gipps Model and Minimising Overall Braking Induced by Lane Changes (MOBIL) [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption is over‐simple due to the effects of interactions between the subject vehicle and its surrounding vehicles on lane change decisions actually exist in the lane change process. To better understand the decision‐making of a lane change, a game‐theoretical approach was used to quantitatively characterise the interactions between human drivers [14]. This approach has been widely applied in recent studies [15–18].…”
Section: Introductionmentioning
confidence: 99%